The Method of Trig Substitution

The Method of Trig Substitution - The Method of...

Info iconThis preview shows pages 1–10. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: The Method of Trigonometric Substitution Main Idea The method helps dealing with integrals, where the integrand contains one of the following expressions: (where a and b are constants) b ax bx a bx a- +- 2 2 2 A simpler forms of the former expressions are the following ones : 1 1 1 2 2 2- +- x x x To get rid of the root, we substitute sin θ , tan θ or sec θ respectively The radical Substitution The radical becomes dx becomes x = sin θ cos θ cos θ d θ x = tan θ sec θ sec 2 θ d θ x = sec θ tan θ sec θ tan θ d θ 2 1 x- 2 1 x + 1 2- x To apply that to the general cases, we transfer the radical to a form similar to the respective simple form 2 2 2 2 ) ( 1 x a x b a a b- =- 2 2 2 2 ) ( 1 x a x b a a b + = + 1 ) ( 2 2 2 2- =- x a a x b a b The First Case We let: sin θ = (b/a)x → x = asin θ /b → dx = (a/b) cos θ d θ The radical becomes a cos θ 2 2 2 2 ) ( 1 x a x b a a b- =- The Second Case We let: tan θ = (b/a)x → x = (a /b) tan θ → dx = (a/b) sec 2 θ d θ The radical becomes a sec θ 2 2 2 2 ) ( 1 x a x b a a b + = + The Third Case We let: sec θ = (b/a) x → x = (a /b) sec θ → dx = (a /b) sec θ tan θ d θ The radical becomes a tan θ 1 ) ( 2 2 2 2- =- x a a x b a b Examples...
View Full Document

This note was uploaded on 10/12/2011 for the course MATH 201 taught by Professor Foad during the Spring '11 term at Qatar University.

Page1 / 36

The Method of Trig Substitution - The Method of...

This preview shows document pages 1 - 10. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online